Paradox of choice and the illusion of autonomy: The construction of ethical subjects in right-to-die activism. Issue 5 (28th May 2018) - Gandsman, Ari
ABSTRACT: The right to die is an issue is predicated on larger cultural understandings of autonomy. Autonomy, in turn, is centered around assumptions of choice, that individuals are able to make health-related decisions based on a rational calculation. In such a way, a medically assisted death is differentiated from suicide. Through an ethnographic study of right-to-die activists in North America and Australia and how they understand ideals of "good deaths, " this article will complicate this view by examining the ethical subject constructed by such activism that reveals autonomy to be a useful guiding fiction that mask larger ethical relationships.